2019
DOI: 10.1111/fmii.12122
|View full text |Cite
|
Sign up to set email alerts
|

Investor behaviour and reaching for yield: Evidence from the sterling corporate bond market

Abstract: We provide evidence on how corporate bond investors react to a change in yields, and how this behaviour differs in times of market‐wide stress. We also investigate ‘reaching for yield’ across investor types, as well as providing insights into the structure of the corporate bond market. Using proprietary sterling corporate bond transaction data, we show that insurance companies, hedge funds and asset managers are typically net buyers when corporate bond yields rise. Dealer banks clear the market by being net se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…In the case of assessment methods, local regulators and administrators can develop assessment methods for local green banks, as well as local green credit and banking conditions. The annual results of green bank assessments, as well as some local incentive policies such as interest rate repayment, appropriate financial deposit incentives, and risk sharing, can effectively and appropriately implement the assessment results to promote the sustainability of local green loans (Czech and Roberts-Sklar, 2017).…”
Section: Future Focus and Significance Of Green Developmentmentioning
confidence: 99%
“…In the case of assessment methods, local regulators and administrators can develop assessment methods for local green banks, as well as local green credit and banking conditions. The annual results of green bank assessments, as well as some local incentive policies such as interest rate repayment, appropriate financial deposit incentives, and risk sharing, can effectively and appropriately implement the assessment results to promote the sustainability of local green loans (Czech and Roberts-Sklar, 2017).…”
Section: Future Focus and Significance Of Green Developmentmentioning
confidence: 99%
“…Manconi, Massa, and Yasuda (2012) and Ma, Xiao, and Zeng (2020) find that fixed‐income mutual funds first sold more liquid asset classes, such as Treasury bonds, to meet investor redemptions, at the onset of the financial crisis (Q3‐Q4 2007) and during COVID‐19 pandemic, respectively. Czech and Roberts‐Sklar (2019) find that in the sterling corporate bond market, hedge funds, insurance companies, and asset managers that are typically net buyers, become net sellers in times of stress, such as the Taper Tantrum in 2013. Jian, Li, and Wang (2021) find that unlike tranquil market conditions, during heightened market uncertainty CBMF managers scale down liquid and illiquid asset classes proportionally.…”
Section: Introductionmentioning
confidence: 99%
“…With the strengthening of the government's macro-control, especially the control of the real estate loan business by the banking industry and the increase in loan interest rates, the financing of real estate companies' investment projects appears more difficult along with the cost being increased, which has forced real estate companies to make major changes in financing methods-Bank loans have diversified into financing methods. Since the unbundling of Real Estate Company debt financing, corporate bonds have become an increasingly important financing channel for real estate companies (Czech & Roberts-Sklar, 2019). However, due to China's mounting supervision in 2017, the proportion of real estate corporate bonds has sharply fallen, and bond issuance rates have continued to rise.…”
Section: Introductionmentioning
confidence: 99%
“…Deng (2006) found that compared with developed countries, Chinese individual investors are more inclined to invest in risk-free assets when investing. Honggang (2012) analyzed the relationship between investor risk appetite, risk constraints and capital allocation, and used the VaR model to characterize investor risk appetite (Czech & Roberts-Sklar, 2019).…”
Section: Introductionmentioning
confidence: 99%